Proposed Framework for Integrating 21st Century Skills in intermediate School Biology Textbooks in Iraq - Rasool, Ameer (Al-Adab Journal, 2025)
The research aimed to:Identifying 21st century skills that can be integrated into middle school biology textbooks in Iraq.Analysis of biology books for middle school in Iraq according to 21st century skills.Proposing a framework for integrating 21st century skills into middle school biology textbooks in Iraq.To achieve the research objectives, the researcher used the descriptive analytical method.The research found the following:There is a clear decline in the extent to which some 21st-century skills are included in the biology textbooks for middle school in Iraq.Identification of 21st-century skills in the biology textbooks for middle school in Iraq.A proposed framework for integrating 21st-century skills into the biology textbooks for middle school in Iraq.